Analisis Manajemen Konstruksi Jembatan Kenet Bantul Daerah Istimewa Yogyakarta - Farhan, Ohan (Civil Engineering of Universitas Islam Nahdlatul Ulama Jepara, 2023)
Construction management is the study and practice of the managerial and technological aspects of the construction industry. Construction management can also be interpreted as a business capital carried out by construction consultants in providing advice and assistance in a development project. crowded because this bridge is a connecting access and alternative route to tourist sites in the area. The purpose of this study is to determine the estimated time and cost required to complete this Kenet Bridge Project. The research method used is descriptive quantitative method which focuses on data in the form of numbers or thematics that can be processed and analyzed to produce the necessary data. And for data analysis in this study, including calculation of work volume, work duration, barchart, cost management analysis, cash flow, budget plan, critical path method, and s-curve The results of this study are: 1) Time required to complete This Kenet Bridge Project is estimated to be completed within 190 days (30 weeks), 2) and the estimated cost required for this Kenet Bridge Project is Rp. 9,282,000,000.00 (Nine Billion Two Hundred Eighty Two Million Rupiah).